Non-English Department Students’ Attitude towards the Use of ICT in an English Matriculation Program - Kurniawati, Lemmuela Alvita (Universitas Swadaya Gunung Jati, 2017)
Students’ attitude towards technology use in classroom context is regarded as one of significant elements of the success of ICT integration in teaching and learning context. While the integration of technology in education and its elements have been discussed in literature, the discussion of students’ attitude to such integration in an English matriculation program for university students is still limited. This paper attempted to investigate college non-English major students’ attitude towards the use of Information and Communication Technology (ICT) in an English matriculation program. The data were collected through a questionnaire distributed to 74 students at Duta Wacana Christian University who attended an English matriculation program. The questionnaire employed a 5-point Likert type scale and consisted of three different sections which made of 33 questions in total. The data were quantitatively analyzed using IBM SPSS Statistics 22. An analysis of relationships between students’ attitude to technology in learning English and their gender, age, and program was analyzed using Pearson Product-Moment correlations. Multiple linear regression was also employed to develop statistical model for this study. The findings of this study provided further discussion on the integration of technology in classroom contexts and indicated students’ positive attitude towards the use of ICT in teaching and learning process. Keywords: Information and Communication Technology (ICT), non-English major students, attitude to technology